Developing a European carbon trading market: Will permit allocation distort competition and lead to state aid? - Edwin Woerdman (Fondazione Eni Enrico Mattei (FEEM), 2001)
The objective of this paper is to find out whether differences between the domestic permit allocation procedures of the Member States of the European Union (EU) will distort competition and lead to state aid in a European carbon trading market. This paper shows that it depends whether one takes an efficiency or equity perspective. There is no problem from an efficiency perspective, because both grandfathered and auctioned permits have opportunity costs. However, the competitive distortion and state aid issues are relevant from an equity perspective, because (ceteris paribus) an auctioned firm has less financial resources than its grandfathered competitor abroad. A political (albeit not legal) the Commission in the Danish CO2 emissions trading scheme. The precedent for a European permit trading market is set by the decision of Commission characterised grandfathering as state aid, but nevertheless exempted it by using not only legal and economic, but also political arguments.
Keywords: D63; F18; K32; Q28; Q48; 330; Climate change policy; competitive distortions; emissions trading; European Union; permit allocation; state; Klimaschutz; Emissionshandel; Lizenz; Auktion; Allokation; Wettbewerb; Subvention; EU-Staaten; Dänemark